IMAGE DENOISING TECHNIQUES: LITERATURE REVIEW (International Journal of Engineering and Computer Science, 2014)
In various fields and applications use of images are becoming increasingly popular like in field of medical, education etc. But the problem is that noise will be inevitably introduced in the image during image acquisition process. Another problem that arises after denoising process is the destruction of the image edge structures and introduction of artifacts. For this there are several techniques proposed by other authors for image denoising as well as for edge preservation. In this paper, we aim to provide a review of some of those techniques that can be used in image processing (denoising). This paper outlines the brief description of noise, types of noise, image denoising and then the review of different techniques and their approaches to remove that noise. The aim of this review paper is to provide some brief and useful knowledge of denoising techniques for applications using images to provide an ease of selecting the optimal technique according to their needs.